Utilization Of Mindmeister For The Creation Of Learning Objective Pathways In The Implementation Of The Merdeka Curriculum - Kuswantoro, Agung; Kharismaputra, Aulia Prima; Rahim, Laila; Susanti, Anis (Indonesian Journal of Devotion and Empowerment, 2024)
Merdeka curriculum has been implemented in schools for a few years, but there are still some obstacles to its implementation. Teachers find it difficult to design learning tools, starting from reducing learning outcomes to learning objectives and the flow of learning objectives. One of the solutions is the use of concept maps, which are assisted by the MindMeister application. The goal is for teachers to implement it into a flow of learning objectives. The method of implementing this service is in the form of training teachers with a practical approach. The result of this service is that teachers better understand how to create effective and visually interactive concept maps of learning objectives to plan, organize, and understand learning objectives. This helps teachers and students in carrying out the learning process in a more structured and focused manner. The use of information technology-based applications is very helpful for teachers in learning activities. Teachers must always adapt to any changes and improve their competence with consistent and continuous training, especially related to the use of information technology in learning.